Strategi Pengajaran Guru Dalam Mengatasi Kecemasan Berbicara Siswa - Siti Luruh Ayu Noerjanah; Asprillia Dhigayuka (LP2M IAIN Syekh Nurjati Cirebon, 2022)
Abstract: This present research has specific aims they are:(1)To investigate the students’ speaking difficulties in English Intensive Program. (2) To investigate the speaking anxiety of students in English Intensive Program. (3) To analyze teachers’ teaching strategies in the English Intensive Program conducted in Al-Bahjah II Boarding School Cirebon. This study shows how the teacher’s teaching strategies to overcome the students’ speaking anxiety. This Research used Descriptive Qualitative as a method, in this research, the instrument of the research is the researcher herself. The researcher becomes the source of collecting the data. As the instrument of the research, the researcher took the data carefully and accurately by using two techniques of data collection, namely observation and interview. This research was conducted at Al-Bahjah II Boarding School Cirebon. The respondents are English Teacher and the students of Banat 3 in Al-Bahjah II Boarding School Cirebon. which chosen by strong consideration. The Finding of the research was shown that (1) The students faced some difficulties which comes from external and internal factors. From external factors students have incomprehensible learning input and being left behind by the fluent students in speaking. While, from the internal factors students are lack of vocabulary and grammar mastery. (2) The students in English Intensive Program have two kinds of speaking anxiety namely State and Trait speaking anxiety. State speaking anxiety faced by the students are afraid of being tested and nervous of being monitored by the teacher and afraid to speak in front of the class and being ridiculed by the peers. Besides, the trait speaking anxiety faced by the students are lack of confident and high tension of nervous. (3) There are five kinds of teaching strategies used by the teacher that considered to overcome the students’ speaking anxiety in English Intensive Program namely, drilling, role play, presentation, group work, show and tell.